57Fe Mössbauer study of unusual magnetic structure of multiferroic 3R-AgFeO2. (7th June 2017) - Sobolev, A; Rusakov, V; Moskvin, A; Gapochka, A; Belik, A; Glazkova, I; Akulenko, A; Demazeau, G; Presniakov, I
Abstract: We report new results of a 57 Fe Mössbauer study of hyperfine magnetic interactions in the layered multiferroic 3 R -AgFeO2 demonstrating two magnetic phase transitions at T N1 and T N2 . The asymptotic value β *   ≈  0.34 for the critical exponent obtained from the temperature dependence of the hyperfine field H hf ( T ) at 57 Fe the nuclei below T N1   ≈  14 K indicates that 3 R -AgFeO2 shows quasi-3D critical behavior. The spectra just above T N1 ( T N1   <   T   <   T  *   ≈  41 K) demonstrate a relaxation behavior due to critical spin fluctuations which indicates the occurrence of short-range correlations. At the intermediate temperature range, T N2   <   T   <   T N1, the 57 Fe Mössbauer spectra are described in terms of collinear spin-density-waves (SDW) with the inclusion of many high-order harmonics, indicating that the real magnetic structure of the ferrite appears to be more complicated than a pure sinusoidally modulated SDW. Below T   <   T N2   ≈  9 K, the hyperfine field H hf reveals a large spatial anisotropy (Δ H anis   ≈  30 kOe) which is related with a local intra-cluster (FeO6 ) spin-dipole term that implies a conventional contribution of the polarized oxygen ions. We proposed a simple two-parametric formula to describe the dependence of H anis on the distortions of the (FeO6 ) clusters. Analysis of different mechanisms of spin and hyperfine interactions in 3 R -AgFeO2 and its structural analogue CuFeO2 points to a specific role played by the topology of the exchange coupling and the oxygen polarization in the delafossite-like structures.